2023
DOI: 10.1097/md.0000000000034923
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial involving college student: Comparing 0.15% hyaluronic acid with 0.05% cyclosporine A and 3% diquafosol sodium in the Treatment of Dry Eye

Wenhao Xu,
Xinrui Zhao,
Haiyan Jin
et al.

Abstract: Background: To compare the efficacy of 0.15% hyaluronic acid (HA), 0.05% cyclosporine A (CsA) and 3% diquafosol sodium (DQS) ophthalmic solution for the treatment of moderate-to-severe dry eye disease (DED) in college students and the effect on inflammatory factors in tears. Methods: This was a prospective, randomized, multicenter trial. A total of 282 college students diagnosed with moderate-to-severe DED between October 2, 2022 and March 1, 2023 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Tear film instability increases the risk of corneal epithelial injury, which leads to the release of inflammatory mediators. Immune cells on the ocular surface release a large number of proinflammatory cytokines, which recruit more immune cells to accumulate on the ocular surface, leading to a vicious circle of inflammation [ 35 ]. This study showed a significant reduction in tear inflammatory cytokine levels at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Tear film instability increases the risk of corneal epithelial injury, which leads to the release of inflammatory mediators. Immune cells on the ocular surface release a large number of proinflammatory cytokines, which recruit more immune cells to accumulate on the ocular surface, leading to a vicious circle of inflammation [ 35 ]. This study showed a significant reduction in tear inflammatory cytokine levels at 3 months.…”
Section: Discussionmentioning
confidence: 99%